KAJIAN BANDINGAN DESAIN VISUAL SITUS PRODUK FURNITUR IKEA DAN OLYMPIC PERIODE 2015 - JESSICA YONATIA (Serat Rupa: Journal of Design, 2016)
Nowadays as technology grows and globalization affects, most companies usually have product catalogues on website as an advertising and online shopping as well. The study attempts to identify visual appearance comparison of Ikea and Olympic websites, by aesthetic elements which suit to visual communication design's principles. The applied method is qualitative method supported by theories and field survey. The result will be outlined as descriptive analysis which may be a reference in making an effective, informative and visually aesthetic commercial website.Â Keywords: aesthetic; commercial website; online; visual communication design